Survey on technical management of strawberries in Morocco and evaluation of their post-harvest microbial load - Abir El-araby; Amal Azzouzi; Iman Msegued Ayam; Khaoula Filali Samouh; Faouzi Errachidi (Frontiers in Microbiology, 2023)
The climatic conditions of the growing regions influence the fruit’s microbiological quality and their tolerance to post-harvest pathogens. The present work aims to identify the prevalence of bacterial and fungal strains of strawberries (Fragaria × ananassa) in the Gharb and Loukkos regions of Morocco. Thus, to establish a correlation between the microbial load and the climatic conditions of the two targeted regions. The bacteriological analyses were studied according to the International Organization for Standardization (ISO) methodologies. Regarding the mycological study, fungal species determination was performed using identification keys. Yeast species determination was done using genus analysis, assimilation, and fermentation tests. Emberger bioclimatic quotients (Q2) were calculated for the Gharb and Loukkos regions and bioclimatic stages were determined. Salmonella spp. was not detected in the studied samples. However, Listeria monocytogenes and Escherichia coli were isolated from the Gharb samples. Sulfite-reducing clostridia spores were found in two Gharb samples versus one Loukkos sample. Coagulase-positive staphylococci were negative in all samples analyzed. Loukkos and Gharb regions were contaminated by Bacillus cereus with percentages of occurrence of 5.2 and 7.8%, respectively. The fungi found in strawberries from both regions were Aspergillus niger, Botrytis cinerea, Fusarium spp., Penicillium spp., Rhizopus spp., and Alternaria alternata with a significant predominance in the Loukkos samples. Indeed, a marked presence is noted for Candida sake and Rhodotorula glutinis in strawberries from Loukkos. Gharb is located on the semi-arid stage, while Loukkos is located on the sub-humid stage. Climatic conditions have a strong influence on plant microbial load, which explains the prevalence of bacteria in strawberries from Gharb and the prevalence of fungi in strawberries from Loukkos.